The Effect of Aided Language Stimulation (ALS) Strategy in Improving Expressive Language of Children with Cerebral Palsy - Warahmah, Mega Sri; Aprilia, Imas Diana (Department of Special Education, 2024)
Cerebral Palsy children have difficulty in terms of language skills and expressing their desires. The barrier is called the expressive language barrier. Expressive language barriers are characterized by speech delays that do not even develop, so they have difficulty interacting and communicating with their environment. Based on the explanation, it is important to research the use of an aided language stimulation strategy. The purpose of this study was to see the effect of the aided language stimulation strategy on increasing the expressive language of children with cerebral palsy. This study uses a quantitative approach with a single-subject research type with an A-B-A research design. The research subjects in this study were a boy and a girl in second grade with cerebral palsy. The information collection techniques use action tests. The information is processed and analyzed using descriptive statistical analysis of conditions and between conditions, then presented in the form of a table and graph. Based on the research result, showed that there was an effect of aided language stimulation strategy on the subject's expressive language development. This can be seen from the baseline results of the two subjects, namely subject R at baseline-1 was 30%, in the intervention phase (B) was 48.75%, and at baseline-2 was 58.75%. The results for subject N at baseline-1 was 20%, intervention phase (B) was 40.62%, and at baseline-2 phase was 52.5%.